Dano intelectual por violação do direito à educação fundamental pública de qualidade - Watzel, Ricardo de Azevedo (2021)
This is a Master’s degree dissertation on the civil liability of the State in the scope of the deficient public elementary education, a relation from which stems what has been called intellectual damage. The aim of this study is to introduce this new category of damage. It was a bibliographic and documental research, using the qualitative and explanatory methods. It was observed, in this study, that the evolution of civil liability may generate legal instability, mainly when considering reparation. In the same sense, the legal internal statutes become sometimes, harmless in face of the government reality, serving merely as rhetoric and demagogy. The conclusions point to the need of a new look at civil liability, so that the more complex relations can resort to a model of responsibility which reduces the social cost of the damage, that is, having more the aim of preventing than that of repairing. However, the impact caused by the intellectual damage on the individual, on society and on the State itself also requires repressive measures. In the case of Brazil and Latin American countries which suffer this type of damage, the Inter-American System may safeguard the right and address the shortcomings of the internal plan of the States. The Inter-American Court on Human Rights, however, usually judges only paradigmatic cases, which requires a wide recognition of the intellectual damage resulting from a dangerous relationship (in the sense of a “mise en danger”) causing effects which prevent the full development of the individual and the State.